2015
DOI: 10.3329/bjms.v14i4.16257
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Modified Alvarado Score in Diagnosis of Acute Appendicitis in Adults

Abstract: Abstract:Background: Definitive diagnosis of acute appendicitis preoperatively is sometimes difficult. Failure to make a diagnosis is the main reason for persistent rate of morbidity and mortality. Various scoring systems are devised to aid diagnosis of acute appendicitis. In some studies the modified Alvarado score was helpful, reliable and practical in minimizing unnecessary appendectomy. Objective: The purpose of this study was to evaluate the usefulness of modified Alvarado score for the diagnosis of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Our study showed a higher incidence of acute appendicitis in the age group 20-29 (54%) which represents the incidence in the adult population. A similar age incidence was reported in many studies that excluded children from the developing world (31)(32)(33), however, some studies, reported high incidence in the third decade (34).…”
Section: Discussionsupporting
confidence: 82%
“…Our study showed a higher incidence of acute appendicitis in the age group 20-29 (54%) which represents the incidence in the adult population. A similar age incidence was reported in many studies that excluded children from the developing world (31)(32)(33), however, some studies, reported high incidence in the third decade (34).…”
Section: Discussionsupporting
confidence: 82%